Determination of Porosity and Permeability of Darnah Formation at Al-Jabal Al-Akhdar-North Eastern Libya - Khorshid , Salman Z. (Iraqi Journal of Science, 2022)
The study area is located at AL Jabal AL-Akhdar region North Eastern part of Libya. The study includes (23) fresh samples that are taken from Darnah limestone Formation, these samples were distributed on and covered about (210) km2. The porosities and permeabilities of these samples were determined. This study is important because this formation is considered as a good reservoir for hydrocarbon accumulation in other places in Libya.The porosity was measured by three different methods namely by porosimeter (using core samples), thin sections and binocular microscope. The permeability are also measured by two methods, the first method was by Nitrogen method and the other is by Klinkenberg method. The instrument that used for measuring permeability is Permeameter, which is found in Arabian Gulf Oil Company Laboratories (AGOCO) in Benghazi.Comparing the porosities by these three methods, it was clear that the porosity which was measured by porosimeter is better than the other two methods, because this instrument gives porosity by 3-Dimensions using core samples, but the other two methods give porosity in 2-Dimensions.The results show that the range of porosities measured by porosimeter was between (2.3% - 29.8%), the range by thin sections was between (2% - 23%) and the range by binocular microscope was between (4% - 29%). On other hand the range of permeabilities by Nitrogen method was found between (0.1 – 1572) millidarcy, and by Klinkenberg method was between (0.05 – 1506) Millidarcy. This variety of the range depends on the locations of samples as well as on active and inactive porosities, so there is no significant difference between the porosities and permeabilities of the same sample